The Influence of Learning Orientation, Strategic Renewal, and ICT Usage on Organizational Performance through Innovation Capability - Anwar T; Amrin; Muhammad Ilham (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the influence of learning orientation, strategic renewal, and information and communication technology usage on organizational performance through innovation capability in Indonesia’s automotive component industry. Using a quantitative descriptive-verificative design with Structural Equation Modeling (SEM), the research surveyed 248 companies selected from 362 units in Jakarta, Banten, and West Java through purposive sampling. Respondents were company leaders or owners. The findings show that learning orientation and innovation capability usage positively affect both innovation capability and organizational performance. Strategic renewal, however, only directly influences organizational performance without significantly affecting innovation capability. Furthermore, innovation capability plays a mediating role, strengthening the impact of learning orientation, strategic renewal, and innovation capability usage on organizational performance. These results highlight the importance of fostering innovation in services and processes, supported by innovation capability adoption, to enhance competitiveness and productivity in the national automotive component industry. The study provides practical insights for industry leaders in making strategic decisions to adapt to intense market competition.